A Newly Isolated Bacillus subtilis Strain Named WS-1 Inhibited Diarrhea and Death Caused by Pathogenic Escherichia coli in Newborn Piglets - Du, Yunping; Xu, Zhichao; Yu, Guolian; Liu, Wei; Zhou, Qingfeng; Yang, Dehong; Li, Jie; Chen, Li; Zhang, Yun; Xue, Chunyi; Cao, Yongchang (Frontiers in Microbiology, 2019)
Bacillus subtilis (B. subtilis) are recognized as safe and reliable human and animal probiotics related with bioactivities such as production of vitamin and immune stimulation. Additionally, it has a great potential to be used as an alternative of antimicrobial drugs, which means more in the context of antibiotic abuse in food animal production. In this study, we isolated one strain of B. subtilis, named WS-1, from apparently healthy pigs growing with sick cohorts on one Escherichia coli (E. coli) endemic commercial pig farm in Guangdong, China. WS-1 can strongly inhibit the growth of pathogenic E. coli in vitro. B. subtilis WS-1 strain has typical Bacillus characteristics by morphology observation, Gram's staining, biochemical test, enzyme activity analysis and 16S rRNA sequence analysis. Genomic analysis showed that B. subtilis WS-1 strain share 100% genomic synteny with B. subtilis with a size of 4,055,167 bp. Importantly, inoculation of newborn piglets with 1.5 × 1010 CFU of B. subtilis WS-1 strain by oral feeding could obviously inhibit diarrhea and death caused by pathogenic E. coli in piglets. Furthermore, histopathological results showed that WS-1 strain could protect small intestine from lesions caused by E. coli infection. Collectively, these findings suggest that the probiotic B. subtilis WS-1 strain act as a potential biocontrol agent protecting pigs from pathogenic E. coli infection.